MHD free convective flow past a vertical plate - Mohamad Asimoni, Nor Raihan; Mohammad, Nurul Farahain; Kasim, Abdul Rahman Mohd; Shafie, Sharidan (IOP Publishing, 2017)
The free convective flow in incompressible viscous fluid past a vertical plate is studied under the presence of magnetic field. The flow is considered along the vertical plate at x-axis in upward direction and y-axis is taken normal to it. The governing equations are written in vector form. Afterwards, the equations are solved numerically using finite element method with automated solution techniques. Later, the effects of magnetic field strength to the velocity and temperature of the fluid are obtained. It is found that for heated plate, the velocity and the temperature of the fluid decreases when the magnetic field strength increases. Meanwhile for cooled plate, the velocity decreases but the temperature increases when the magnetic field strength increases.